Effects of methanol extract of desmodiumvelutinum stem on some biochemical parameters in acetaminophen intoxicated rats - CHINELO NKWOCHA,; ONYINYECHI NWAGWE, (International Journal of Pharma and Bio Sciences, 2018)
The effects of methanol extract of Desmodiumvelutinum stem on liver function biomarkers, kidney function biomarkers, serum electrolyte levels and lipid profile of acetaminophen-intoxicated rats. A significant increase (P<0.05) was observed in the serum activities of AST, ALT, ALP, and levels of bilirubin and total protein content of rats in group two when compared with group 1, which indicates that the acetaminophen may induce hepatic dysfunction. However, the serum activities of AST, ALT and ALP, and concentrations of bilirubin and protein of rats pre-treated with methanol extract of D. velutinum stem and silymarin were significantly (p < 0.05) lower when compared with the intoxicated and untreated rats. A significantly (p < 0.05) higher mean serum of TC, LDL and TAG, and lower HDL levels of rats in group 2 compared with that of group 1 (normal control). Serum total urea and creatinine levels of rats in group 2 were significantly (p < 0.05) higher than those of rats in the intoxicated - treated (groups 3- 6), and normal control (group1) groups. Similarly, the serum chloride levels of animals in groups 2 were significantly (p < 0.05) higher than those of animals in the intoxicated and treated and normal rats